2019
DOI: 10.2174/1574888x14666190123162402
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Functional Roles of miRNAs in Embryonic and Lineage-Specific Stem Cells

Abstract: The discovery of small non-coding RNAs began an interesting era in cellular and molecular biology. To date, miRNAs are the best recognized non-coding RNAs for maintenance and differentiation of pluripotent stem cells including embryonic stem cells (ES), induced pluripotent stem cells (iPSC), and cancer stem cells. ES cells are defined by their ability to self-renew, teratoma formation, and to produce numerous types of differentiated cells. Dual capacity of ES cells for self-renewal and differentiation is contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 126 publications
1
8
0
Order By: Relevance
“…MiRNAs represent the key "fine-tuners" of gene expression during the differentiation of hPSCs. It has been previously shown that manipulation with single miRNA or the whole miRNA cluster/family may have a significant impact on differentiation outcomes of pluripotent stem cells [16][17][18][19]. Here we show that the miR-183/96/182 cluster regulates PAX6 expression in differentiating hPSCs into retinal organoids.…”
Section: Discussionsupporting
confidence: 52%
“…MiRNAs represent the key "fine-tuners" of gene expression during the differentiation of hPSCs. It has been previously shown that manipulation with single miRNA or the whole miRNA cluster/family may have a significant impact on differentiation outcomes of pluripotent stem cells [16][17][18][19]. Here we show that the miR-183/96/182 cluster regulates PAX6 expression in differentiating hPSCs into retinal organoids.…”
Section: Discussionsupporting
confidence: 52%
“…MiRNAs represent the key “fine‐tuners” of gene expression during the differentiation of hPSCs. It has been previously shown that manipulation with single miRNA or the whole miRNA cluster/family may have a significant impact on differentiation outcomes of pluripotent stem cells 16‐19 . Here, we show that the miR‐183/96/182 cluster regulates PAX6 expression in differentiating hPSCs into retinal organoids.…”
Section: Discussionmentioning
confidence: 52%
“…It has been previously shown that manipulation with single miRNA or the whole miRNA cluster/family may have a significant impact on differentiation outcomes of pluripotent stem cells. [16][17][18][19] Here, we show that the miR-183/96/182 cluster regulates PAX6 expression in differentiating hPSCs into retinal organoids. its expression is necessary for eye formation and retinal development.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional differentiation methods compared with the novel growth factor-and serum-free culture approaches for erythroid differentiation of human iPSCs therefore conceivable that HDAC2 activators may enhance chromatin condensation of iPSC-derived erythroid cells [141]. MicroRNAs are important regulators that downregulate the expression of target genes [142,143] and improve the maintenance of immature hematopoietic cells and terminal erythroid differentiation [58,143]. Therefore, different combinations of microRNAs may increase the numbers of iPSC-derived mature RBCs [139].…”
Section: Primary Technical Challenges For the Clinical Application Ofmentioning
confidence: 99%